THE INFLUENCE OF COMPUTER-BASED INTERACTIVE MEDIA AND STUDENTS' CRITICAL THINKING SKILLS ON LEARNING OUTCOMES OF PHYSICS MATERIAL ELASTICITY OF CLASS XI IPA STUDENTS AT SMA PAKUSARI - Pungkasaningsih sri; Abdul muis (Journal of Education Technology and Inovation, 2022)
The influence of computer-based interactive media has an influence on critical thinking skills and learning outcomes of physics material Elasticity. Respondents of this study were students of class XI IPA SMAN Pakusari, With a total of 76 students in Class XI IPA 4 with computer-based interactive learning with the MS team application in the 2020 school year, the research area was determined using the purpuse sampling area method. This research is a quantitative research with causal quantitative design. Data collection tools using observation, interviews, documentation and tests. Test Analysis of the instrument using: 1) normality test 2) homogeneity test. Data analysis used multiple linear regression using the product moment. Based on the hypothesis test, it is proven that: (1) the results of the 1-Sample Kolmogorov Smirnov analysis above, obtained the data sig = 0.088. Because the obtained sig > 0.05, then H0 is accepted, Ha is rejected. That is, the experimental class = control class.2). Based on the "Paired Sample Correlation" table above, the correlation value is 0.209 with a significance of 0.220. Because the significance value is > 0.05, it can be said that there is no relationship between the pretest variable and the posttest variable. Based on the table "Paired Sample t-test", it was found that the significance value (2-tailed) was 0.00. Because the significance value is <0.05, then H0 is rejected and Ha is accepted. So it can be said that there is an average difference between the pretest and posttest scores, which means that the use of Ms. Teams can improve student learning outcomes and critical thinking skills on physics material